Advanced Computational Methods for Knowledge Engineering : Proceedings of the 6th International Conference on Computer Science, Applied Mathematics and Applications, ICCSAMA 2019 /: Proceedings of the 6th International Conference on Computer Science, Applied Mathematics and Applications, ICCSAMA 2019. (2020) - Unknown
No abstract available